THE RELATIONSHIP BETWEEN HUMOR STYLE AND DEATH ANXIETY OF PALLIATIVE CARE PATIENTS - Tuğba MENEKLİ; Runida DOĞAN (Rojan GÜMÜŞ, 2021)
This descriptive and relational study was conducted to examine the relationship between palliative care patients' humor styles and death anxiety. The study sample consisted of 282 palliative care patients treated in the palliative care clinics of a training and research hospital between January 2021 and August 2021. Personal Information Form, Humor Styles Questionnaire, Thorson-Powell Death Anxiety Scale, and Palliative Performance Scale were used as data collection instruments. Data analysis was performed using mean, standard deviation, and percentile, Kolmogorov-Smirnov Goodness-of-Fit Test, Significance test of the difference between two means, ANOVA, Post-hoc test, Pearson's Correlation test, and regression analysis. It was found that the mean age of the patients was 49.58±9.56 and 52.1% were hospitalized in the palliative care clinic for 5-10 days. It was determined that the most frequently used humor style by the patients was "Affiliative Humor" (31.7%), and the least used humor style was "Aggressive Humor" (19.5%). The Humor Styles Questionnaire subscale scores of the patients were determined as 31.05±7.11, self-enhancing humor 28.34 ± 6.94, aggressive humor 26.85±7.37, self-defeating humor 23.50± 6.21. The death anxiety scale mean scores of the patients were found to be 81.62±9.12. In addition, a low negative correlation was found between affiliative humor (r=-0.298; p<0.05) and self-enhancing humor (r=-0.318; p<0.05) and death anxiety. A moderate positive correlation was found between aggressive humor (r=0.450; p<0.05) and self-defeating humor (r=0.427; p<0.05) and death anxiety. The result of the study revealed that humor is an important variable associated with death anxiety and the way humor is used by patients differs in death anxiety.